Neonatal screening tests in Brazil: prevalence rates and regional and socioeconomic inequalities - Mariana B. Mallmann; Yaná T. Tomasi; Antonio Fernando Boing (Brazilian Society of Pediatrics, 2020)
Objective: To identify the prevalence and associated factors with the performance of the Guthrie test, hearing, and red reflex screening tests in Brazil. Methods: This was a population‐based, cross‐sectional study that analyzed data on 5,231 children under 2 years of age participating in the National Health Survey of 2013. The study described the prevalence and Confidence Intervals (95% CI) of the three neonatal screening tests performed, in any period, and their association with the country's regions, skin color/ethnicity, private health insurance, and per capita household income. Logistic regression models were used, and odds ratios were calculated by incorporating sample weights. Results: The prevalence of Guthrie test screening in Brazil at any time of life was 96.5%, that of the newborn hearing screening was 65.8% and that of the red reflex screening test was 60.4%. The performance of the three screening tests was significantly higher among children whose mothers/guardians reported higher per capita household income, who lived in the South and Southeast regions, and who had private health insurance (p < 0.001). There was no statistically significant difference regarding the performance of the tests according to skin color/ethnicity (p > 0.05). The same inequalities were verified when the tests were performed during the recommended periods, with a strong socioeconomic gradient. Conclusions: There are inequalities in the performance of neonatal screening tests in the country, and also in the performance of these tests during the periods established in the governmental guidelines. The guarantee of the performance of these tests in a universal and public health system, as in Brazil, should promote equity and access to the entire population. Resumo: Objetivo: Identificar prevalência e fatores associados à realização dos testes do pezinho, da orelhinha e do olhinho no Brasil. Método: Estudo transversal analítico de base populacional que analisou os dados de 5.231 crianças menores de dois anos participantes da Pesquisa Nacional de Saúde (2013). Foram descritas prevalências e intervalos de confiança (95% IC) da realização dos três testes de triagem neonatal, em qualquer período, e sua associação com as regiões do país, cor/etnia, posse de plano de saúde e renda domiciliar per capita. Empregaram‐se modelos de regressão logística e calcularam‐se as odds ratio e incorporaram‐se os pesos amostrais. Resultados: A prevalência de realização do teste do pezinho no Brasil em qualquer momento de vida foi de 96,5%; do teste da orelhinha de 65,8% e do teste do olhinho de 60,4%. A realização dos três testes de triagem foi significativamente maior entre as crianças cujas mães/responsáveis reportaram maior renda domiciliar per capita, residiam nas regiões Sul e Sudeste e tinham plano de saúde (p < 0,001). Não houve diferença estatisticamente significativa na realização dos testes segundo cor/etnia (p > 0,05). As mesmas desigualdades foram verificadas para a realização dos testes no período preconizado, com forte gradiente socioeconômica. Conclusões: Existem desigualdades na realização dos testes de triagem neonatal no país e, também, na realização desses dentro dos prazos previstos nas diretrizes governamentais. A garantia desses testes em um sistema universal e público como no Brasil deveria promover a equidade e o acesso a toda a população.